Perancangan Produk Hand Sanitizer Untuk Mencegah Penyebaran Covid 19 Di Desa Kalitorong, Randudongkal, Pemalang, Jawa Tengah - Alfatiyah, Rini; Bastuti, Sofian; Candra, Adi; Trihandayani, Estiningsih; Mualif, M. (LPPM Universitas Pamulang, 2020)
Indonesia is still struggling against the Corona virus to date, the number of cases of the Corona virus continues to grow with several reports of recovery, but not a few who died. This PKM activity was carried out in Central Java province which included 10 provinces with the most cases of COVID-19. This PKM activity is precisely carried out in Kalitorong village, Randudongkal sub-district, Pemalang, Central Java, Indonesia. The problem that will be solved in this activity is how to break the distribution chain of COVID-19. The method that will be used in this community service is through online counseling, discussion and simulation activities, with materials to prevent the spread of COVID-19 and Hand Sanitizer Product Design. The result is to look at the results of the questionnaire respondents who are very understanding 11 people or 45.83%, understand 12 people or 50%, lack of understanding 1 person or 4.17%, meaning that respondents can make hand sanitizer products and can be developed as business products and as a prevention of the spread of Covid-19.